Analisis Pengaruh Ekowisata Terhadap Pendapatan Pengrajin Kerang Di Kawasan Kampung Blekok Situbondo - Firdaus, Arif Rahman; Listriyana, Ani; Handayani, Creani (Jurnal Manajemen Pesisir dan Laut, 2024)
Community welfare is greatly influenced by its economic conditions. In Indonesia, tourism is one of the main economic sectors, as evidenced by the high number of tourist and the income generated every year. Ecotourism, especially natural tourism, is developing as a form of environmentally friendly tourism. Kampung Blekok in Situbondo is an example of ecotourism development with a focus on mangrove forests and shell crafts. This research aims to evaluate the impact of ecotourism on the income of the shellfish craft community in Kampung Blekok. The method used is quantitative with descriptive data analysis. The research results show that Kampung Blekok ecotourism has a positive impact on the income of shellfish craftsmen. Before ecotourism existed, they only sold their products for export or sold outside the region. However, after ecotourism exists they can sell directly in tourist areas. The average income of craftsmen increased by 10.15% after the introduction of ecotourism.